RETRACTED: HUBUNGAN PENGETAHUAN SISWI TENTANG DISMENOREA DENGAN PERILAKU PENANGANAN DISMENOREA - Monifa Putri; Maisel Oktabela (STIKes Al-Insyirah Pekanbaru, 2019)
ABSTRACK Dysmenorrhoea is menstrual pain that feels in the lower abdomen and appears before, during or after menstruation. Pain can be colic or continuous. This study aims to determine the relationship of the level of student knoeledge about dysmenorrhoea with handling behavior in SMAN 1 Rengat. The method used is analytic with the sampling technique that is accidental sampling, the way to collect data using primary data through interviews. The results showed that of the 90 respondents at SMAN 1 Rengat, out of 23 students (25.5%) who had good knowledge who behaved positively in handling dysmenorrhoea were 21 people (24.1%) and none of them behaved negatively, out of 53 students (58.9%) who had sufficient knowledge who behaved positively in handling dysmenorrhoea amounted to 52 people (59.8%), and who behaved negatively amounted to 1 person (33.3%), out of 14 students (15.6%) who had knowledge less who behaved positively in handling dysmenorrhoea amounted to 14 people (15.6%), and those who behaved negatively totaled 2 people (66.7%).